Estimating inequalities in excess mortality and years of potential life lost by health conditions across ethnic minorities in Colombia: a population-based study, 2018-2022 - Rocco Friebel; Valeria Bejarano; Oscar Espinosa; Johnattan García-Ruiz (BMJ Open)
Objectives This study aims to compare the burden of excess mortality and years of potential life lost by cause of death and geography for minority groups to inform targeted policy development.Design Population-based study using information from the National Administrative Department of Statistics.Setting National and subnational level (departments, urban and rural areas).Participants Individuals of all age groups classified as Indigenous, Romani, Raizal, Afro-Colombian and Mestizo in Colombia between 1 January 2018 and 31 December 2022.Primary and secondary outcome measures Excess mortality and years of potential life lost were calculated for all ethnic-racial groups by cause of death and subnational level expressed per 100 000 population.Results Our study included 1 420 258 total deaths and we observed significant variation across ethnic-racial groups. Excess mortality and years of potential life lost were most pronounced in Raizal (total of 145 more deaths and 11 769 more years of life lost per 100 000 population) and Romani (total of 7059 more deaths and 85 832 more years of life lost per 100 000 population) populations, when compared with Mestizo populations. Higher mortality rates were driven by suicide, pregnancy, childbirth and accidents.Conclusions Our findings indicate that Colombia requires effective strategies to address the unique challenges causing these disparities, ranging from improving access to health services and addressing broader social determinants of health.